2015
DOI: 10.1093/brain/awv226
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic haematopoietic stem cell transplantation for mitochondrial neurogastrointestinal encephalomyopathy

Abstract: Mitochondrial neurogastrointestinal encephalopathy (MNGIE), usually an autosomal-recessive inherited condition, causes gastrointestinal dysmotility, ophthalmoplegia, ptosis, leukoencephalopathy and neuropathy. The chromosome 22 disorder, due to mutations in the nuclear gene TYMP encoding thymidine phosphorylase (TP), leads to the accumulation of thymidine and deoxyuridine, with mitochondrial dysfunction. This report describes a patient with an MNGIE-like syndrome with a heterozygous TYMP mutation who showed ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
162
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 132 publications
(167 citation statements)
references
References 27 publications
2
162
0
3
Order By: Relevance
“…21,24 Only allo-HSCT has been demonstrated to be metabolically and clinically effective and associated with objective evidence of health improvement in the long-term. 13,14 However, this procedure has produced high morbidity and mortality rates in MNGIE patients. 13 In recent years, gene therapy has emerged as a promising alternative for MNGIE patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…21,24 Only allo-HSCT has been demonstrated to be metabolically and clinically effective and associated with objective evidence of health improvement in the long-term. 13,14 However, this procedure has produced high morbidity and mortality rates in MNGIE patients. 13 In recent years, gene therapy has emerged as a promising alternative for MNGIE patients.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, this procedure has produced high morbidity and mortality rates in MNGIE patients. 13 In recent years, gene therapy has emerged as a promising alternative for MNGIE patients. Our previous work has demonstrated that ex vivo hematopoietic stem cell gene therapy (HSCGT) using a lentiviral vector was able to provide ectopic TP activity in blood cells for at least six months after transplantation of sublethally irradiated Tymp/ Upp1 dKO mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question of whether leukoencephalopathy is a reversible feature cannot be solved at present. Long-term follow-up of patients with bone marrow 34,35 and liver transplantation 36 will likely provide an answer.…”
Section: Resultsmentioning
confidence: 99%